2021
DOI: 10.3390/jcm10184137
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Clinical Findings and Severity of Diffuse Idiopathic Skeletal Hyperostosis in Patients with Ossification of the Posterior Longitudinal Ligament

Abstract: Background: This study investigated how diffuse idiopathic skeletal hyperostosis (DISH) influences clinical characteristics in patients with cervical ossification of the posterior longitudinal ligament (OPLL). Although DISH is considered unlikely to promote neurologic dysfunction, this relationship remains unclear. Methods: Patient data were prospectively collected from 16 Japanese institutions. In total, 239 patients with cervical OPLL were enrolled who had whole-spine computed tomography images available. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The Modified New York Criteria [35] defines AS based on radiographic features, including sacroiliitis grade ≥ 2 bilaterally or grade 3-4 unilaterally. Although vertebral ossification bridging can be found in DISH and/or OPLL [36,37] with morphology similar to that of AS, bone formation in patients with ossification differs from that in AS patients on a basic level. The bridging formation in ossification patients often has a candle-wax pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The Modified New York Criteria [35] defines AS based on radiographic features, including sacroiliitis grade ≥ 2 bilaterally or grade 3-4 unilaterally. Although vertebral ossification bridging can be found in DISH and/or OPLL [36,37] with morphology similar to that of AS, bone formation in patients with ossification differs from that in AS patients on a basic level. The bridging formation in ossification patients often has a candle-wax pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in cervical OPLL in patients with ankylosing spondylitis, reconstruction surgery with rigid fixation should be applied for the affected levels adjacent to the lesion. Interestingly, the prevalence of diffuse idiopathic skeletal hyperostosis (DISH) w shown to be approximately 45% in cervical OPLL patients [34,35]. Other observational studies have also demonstrated that multiple ossified lesions in the cervical spine often coexist with ossification of the spinal ligaments in the thoracolumbar spine [34,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted by the Japanese Multicenter Research Organisation for Ossification of the Spinal Ligament with the assistance of the Japanese Ministry of Health, Labour and Welfare. This study was performed using ossification of the posterior longitudinal ligament whole spine CT database, in which 50% of the patients have co-existing DISH 17 , 18 . DISH was diagnosed with anterior longitudinal ligament ossification in at least four contiguous vertebral bodies as previously reported 17 , 18 .…”
Section: Methodsmentioning
confidence: 99%